Exploring the Neglected Dimensions: The Function and Purpose of Law in Contemporary Society - Bahram, Muhammad (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2025)
This study addresses the growing legal challenges posed by rapid technological development and globalization, particularly in data privacy, intellectual property rights, and consumer protection in the digital era. These developments have created a noticeable gap between existing legal frameworks and the realities faced by contemporary society. This research aims to examine the often-overlooked dimensions of law and to understand how law functions and adapts to ongoing socio-economic and technological changes. The study applies a qualitative method with a conceptual and literature-based approach, focusing on legal theories, statutory regulations, and relevant academic works. The results show that legal systems frequently fall behind technological advancements, leading to regulatory gaps, limited protection of individual rights, and inconsistent enforcement, especially in digital contexts. In addition, current legal frameworks have not fully accommodated the needs of vulnerable groups or responded adequately to emerging technologies. Based on these findings, it can be understood that law needs to become more adaptive and flexible, while also incorporating interdisciplinary perspectives. Strengthening legal responsiveness is therefore essential to ensure effective protection and justice in contemporary society.